The Impact Of Intellectual Capital On Organizational Creativity In Jordanian Health Organizations - Okour, Dr. Karim Saeed (The journal of contemporary issues in business and government, 2021)
The study here was concerned with identifying the intellectual capital and its role in achieving organizational creativity in Jordanian health organizations, as well as verifying the existence of that relationship with that moral link And its moral effect on it, and intellectual capital is linked here with those three elements (human, structural, customers) as well as organizational creativity is divided into three levels (individual, group, organization) and the relative importance of intellectual capital variables becomes evident here in terms of that effect on organizational creativity in those organizations. Jordanian